Optimization of Cream Formulation with Borneo Tallow Nut, Almond Oil, and Olive Oil Using the Simplex Lattice Design Method - Butar-Butar, Maria Elvina Tresia; Taufiqurrahman, Muh; Agus, Adhe Septa Ryant; Sari, Dwi Retno; Selvina, Selvina; Tokan, Santa Eufrasia Carolin (Sciences of Pharmacy, 2024)
Dry skin, a common dermatological issue affecting individuals across all age groups, often disrupts the skin's protective barrier, leading to discomfort and increased sensitivity. Addressing this condition involves the use of moisturizers, which play a vital role in restoring skin hydration. In this study, a cream preparation was successfully developed using vegetable oils, including Borneo Tallow Nut, Almond Oil, and Olive Oil. The cream formula was optimized using the Design-Expert software with the Simplex Lattice Design (SLD) method to evaluate the impact of different concentrations of these oils on the cream's pH, viscosity, spreadability, and adhesion. The results demonstrated that the cream exhibited excellent thermo-physical stability, with optimum values of Borneo Tallow Nut at 1.349% w/w, Almond Oil at 3.598% w/w, and Olive Oil at 4.051% w/w. The cream achieved a pH value of 5.702, viscosity of 16.851 Cp, spreadability of 8.147 cm, and adhesion of 63.682 s, with a desirability score of 0.718. This research confirms that Borneo Tallow Nut, Olive Oil, and Almond Oil have significant potential as excipients in cream formulations.